The Effect of Self-Congruity and Trust Toward Brand Loyalty Based on Image Congruity Theory - Rayhan Bagaskara; Endy Gunanto Marsasi (Indonesian Journal of Economics and Management, 2023)
The purpose of this research is to recognize the influence of self-congruity and trust on brand loyalty in expedition services based on image congruity theory. The number of illustrations taken using 209 people, with universal criteria in Yogyakarta and Central Java. Truts variable becomes a novelty in this research. This research is based on image congruity theory which presents the suitability of cognitive-based self-image with consumer self-concept. The gap in this research is self-congruity, which has different results in previous studies. In this research using quantitative procedures, the method of taking illustrations uses purposive sampling. The information testing process uses IBM SPSS 22 and SEM Application- AMOS 24. The results of this research prove that there are four supported hypotheses and one hypothesis is not supported. Trust on brand loyalty does not affect and is not significant.